Developing an energy audit methodology for assessing decarbonization potential in high performance buildings - Shun Nakayama; Wanglin Yan; Amane Fujita (Energy Conversion and Management: X)
High-performance buildings (HPBs) are designed to minimize environmental impacts during operation, but ensuring continuous efficiency improvements remains a challenge. Existing energy audit methodologies have been developed with limited support of precise operational data. However, the advent of Building Energy Management Systems (BEMS) and the establishment of de facto industry standards for building service and space usage have enabled energy audits to be conducted at an unprecedented level of detail. Taking advantage of these developments, this study proposes an original integrated approach for HPB by combining a standard energy audit framework with BEMS data. The novel method conducts: (1) detailed energy and water consumption profiling across multiple timescales; (2) benchmarking using data envelopment analysis against other HPBs; (3) building diagnostics to identify further carbon reduction opportunities; and (4) marginal abatement cost analysis to explore economically feasible improvement measures for owners. When specifically applied to an HPB in Tokyo, the findings reveal substantial room for further improvements. At least 10.1% in energy saving potential exists compared to the building’s design performance. Moreover, implementing selected cost-effective measures could economically achieve an 8.9% reduction in CO2 emissions. This multifaceted study makes three key original contributions. First, it develops a systematic energy audit methodology tailored to BEMS-equipped HPBs, enabling granular, spatiotemporal analysis of resource consumption. Second, it extends this framework beyond energy to holistically encompass water consumption. Third, it provides quantitative evidence that even highly-rated HPBs may still have significant remaining potential for operational environmental impact reductions, which can be identified in detail through the proposed approach. Overall, by harnessing BEMS data and industry standards, this research demonstrates a feasible and cost-effective pathway for HPB owners and operators to continuously optimize resource efficiency. As the urgency of climate action intensifies, this innovative approach offers a crucial toolkit for the building sector to enhance its contribution to global sustainability goals.